2015
DOI: 10.3748/wjg.v21.i11.3174
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor kappa B role in inflammation associated gastrointestinal malignancies

Abstract: Nuclear factor kappa B (NF-κB) has an established role in the regulation of innate immunity and inflammation. NF-κB is also involved in critical mechanisms connecting inflammation and cancer development. Recent investigations suggest that the NF-κB signaling cascade may be the central mediator of gastrointestinal malignancies including esophageal, gastric and colorectal cancers. This review will explore NF-κB's function in inflammation-associated gastrointestinal malignancies, highlighting its oncogenic contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
69
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 88 publications
3
69
0
1
Order By: Relevance
“…43 Several studies have demonstrated an active NF-κB signaling pathway in CRC and linked the dysregulated NF-κB signaling pathway in colorectal tissue to the malignant transformation, tumor cell proliferation, anti-apoptosis, invasion/metastasis, angiogenesis, and therapeutic resistance. 41,[44][45][46] Evidence indicates that the NF-κB signaling pathway mediates these cellular processes through activation of its target genes comprising numerous growth factors, chemokines and cytokines, c-Myc, cyclin D1, cIAPs, and Bcl-2 family of proteins. Interestingly, the evidence presented by Kim et al 40 that gal-4 regulates NF-κB signaling and the expression of IL-6 in CRC cells lends strong support to our observations presented here that surface-bound gal-4 regulates NF-κB signaling pathway in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Several studies have demonstrated an active NF-κB signaling pathway in CRC and linked the dysregulated NF-κB signaling pathway in colorectal tissue to the malignant transformation, tumor cell proliferation, anti-apoptosis, invasion/metastasis, angiogenesis, and therapeutic resistance. 41,[44][45][46] Evidence indicates that the NF-κB signaling pathway mediates these cellular processes through activation of its target genes comprising numerous growth factors, chemokines and cytokines, c-Myc, cyclin D1, cIAPs, and Bcl-2 family of proteins. Interestingly, the evidence presented by Kim et al 40 that gal-4 regulates NF-κB signaling and the expression of IL-6 in CRC cells lends strong support to our observations presented here that surface-bound gal-4 regulates NF-κB signaling pathway in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear factor (NF)-kappaB (NF-κB) is an important transcriptional factor in the body homeostasis including the maintenance of innate immunity and controlling inflammation, 41,42 and its aberrant regulation is recognized in many human cancers. 43 Several studies have demonstrated an active NF-κB signaling pathway in CRC and linked the dysregulated NF-κB signaling pathway in colorectal tissue to the malignant transformation, tumor cell proliferation, anti-apoptosis, invasion/metastasis, angiogenesis, and therapeutic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It consists of five homologous Rel homology domains (RHD), namely, Rel (p65), RelB, CRel (REI), p50, and p52. 15 Classic NF-κB is a dimer of p50 and p65. 16,17 In an unstimulated state, NF-κB is bound to the inhibitory proteins of the inhibitor of κB (IκB) family by the RHD in the cytoplasm.…”
mentioning
confidence: 99%
“…56 This is most likely due to the fact that NF-κB has been implicated in all the essential steps/processes that drive efficient tumorigenesis. 57 NF-κB has more than hundreds of validated transcriptional targets (http://www.bu.edu/nf-kb/gene-resources/target-genes/), out of which some of them are key players in determining the ability of cancer cells to indefinitely proliferate (cMyc and cyclin D1), inhibit apoptotic signals (ciAPS, c-FLP, and members of the bcl-2 family), migrate (IL-8), undergo angiogenesis (vascular endothelial growth factor (VEGF)) and undergo invasion/metastasis (matrix metalloproteinase (MMP)-2/9)).…”
Section: Nf-κb/relmentioning
confidence: 99%
“…57 NF-κB has more than hundreds of validated transcriptional targets (http://www.bu.edu/nf-kb/gene-resources/target-genes/), out of which some of them are key players in determining the ability of cancer cells to indefinitely proliferate (cMyc and cyclin D1), inhibit apoptotic signals (ciAPS, c-FLP, and members of the bcl-2 family), migrate (IL-8), undergo angiogenesis (vascular endothelial growth factor (VEGF)) and undergo invasion/metastasis (matrix metalloproteinase (MMP)-2/9)). 56,58 Tumor cells achieve constitutive activation of NF-κB by mutations in genes encoding the NF-κB transcription factors themselves or in genes that control NF-κB activity (such as IκB genes). Alternatively, the tumor cells can overexpress growth factors/inflammatory ligands which can induce NF-κB activation.…”
Section: Nf-κb/relmentioning
confidence: 99%